Patterns of Value Creation in Strategic Acquisitions for Growth - Veronika Vinogradova, (Asian Academy of Management Journal of Accounting and Finance, 2023)
This paper extends the previous research on strategic transactions (M&A) and focuses on the analysis of the relationship between the pre-event performance of acquiring companies and value creation in strategic acquisitions for growth. It identifies the prerequisites of successful transactions and tests empirically how the key fundamental determinants of the acquiring companies influence investors’ reaction around the announcement and acquirers’ financial performance in the years after. The results of the analysis confirm that the intrinsic pre-event performance of the acquiring firm can significantly impact the outcome and profitability of strategic M&A.